Understanding and Self-Organization - Newton, Natika W. (Frontiers in Systems Neuroscience, 2017)
This paper asks about the mechanisms by which we rapidly achieve an understanding of our world, both the unexpected changes we may experience, and the ongoing comfortable familiarity we normally have with our surroundings. I attempt a solution by means of fundamental questions like “What is it to understand one’s environment?” The paper concludes that our day-to-day understanding of our environment is the result of a self-organizing process.